Optimal Dispatch of Virtual Power Plant Considering Stepped Carbon Trading and Comprehensive Demand Response - Zhipeng SU; Li WANG; Xinyi LIANG; Tao CHEN; Shunqi ZENG; Zhiwen YU (Zhongguo dianli)
Under the goal of "double carbon", the virtual power plant (VPP) with multi-energy coupling and collaborative operation can effectively reduce the carbon emissions and improve the economic benefits of the system. In order to further reduce VPP carbon emissions and tap the demand side adjustable potential a VPP optimal scheduling model was proposed considering stepped carbon trading and integrated demand response. Firstly, based on the stepped carbon trading mechanism, considering the constraints of each VPP component, a VPP model is established to participate in the carbon trading market. Secondly, the demand response is divided into price demand response and alternative demand response, and the demand response model are constructed respectively. Finally, considering the energy purchase cost, system operation cost and stepped carbon transaction cost, a VPP low-carbon economic operation model is established with the goal of maximizing the benefits of VPP in a scheduling cycle, and the effectiveness of the model was verified by numerical analysis.